2015
DOI: 10.1177/1708538115584506
|View full text |Cite
|
Sign up to set email alerts
|

Individual variations in ankle brachial index measurement among Turkish adults

Abstract: Although reproducibility of ABI values was found satisfactory, up to 12% of participants displayed more than 0.15 alternations between measurements, either on the same day or more than a week apart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 25 publications
(32 reference statements)
1
23
0
Order By: Relevance
“…The majority of studies [12, 4751, 55, 57] included only participants with suspected PAD, or risk factors for atherosclerosis; three studied a mixed population including those without risk factors or clinical indicators of PAD [13, 16, 52]; two studies included only participants with diabetes [53, 54], and two studies included only healthy individuals [46, 56].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies [12, 4751, 55, 57] included only participants with suspected PAD, or risk factors for atherosclerosis; three studied a mixed population including those without risk factors or clinical indicators of PAD [13, 16, 52]; two studies included only participants with diabetes [53, 54], and two studies included only healthy individuals [46, 56].…”
Section: Resultsmentioning
confidence: 99%
“…Methodological limitations related to ABI testing were unlikely in our study due to improved measurement facilities and the guideline recommended calculation of the ABI. However, apart from possible inter-test variations in ABI values obtained at different occasions (24), ABI measurement to diagnose lower extremity PAD may itself not be completely reliable in younger people at the age of early twenties. Although the ABI testing is successful to diagnose PAD (25), its angiographically tested sensitivity was found as low as 79% in different populations (26) and 82.3% in the original population of the study region (27).…”
Section: Discussionmentioning
confidence: 99%
“…The ABI is calculated according to the Trans-Atlantic Inter-Society Consensus Document on Management of Peripheral Arterial Disease II (TASC-II) guidelines 20 . The ABI is calculated by dividing the highest systolic blood pressure measured in each limb (anterior tibial artery or posterior tibial artery) to the highest systolic blood pressure measured in the right or left brachial artery 12 . An ABI < 0.90 is typically accepted to define PAD 11 .…”
Section: Methodsmentioning
confidence: 99%
“…Ankle-brachial index (ABI) is a non-invasive, simple, and routinely used test to diagnose and follow lower-extremity PAD, with a sensitivity of 90% and a specificity of 98% if the value is less than 0.9 11 , 12 . Guerchet et al suggested that a low ABI can be considered a marker of cognitive impairment 11 .…”
Section: Introductionmentioning
confidence: 99%